The Effect of Company Characteristics on Sustainability Report Disclosure with Corporate Governance as Moderating Variable - Tyas, Vivi Ayuning; Khafid, Muhammad (Accounting Analysis Journal, 2020)
The purpose of this study is to obtain empirical evidence about the moderating effect of corporate governance on the effects of profitability, leverage, and firm size towards sustainability report disclosure. The population is the firms listed in the LQ45 index over the period 2015 to 2017 from 40 companies. The sampling technique used in this research is purposive sampling. Seventeen (17) companies were selected in this research with 51 units of analysis were obtained. Regression analysis absolute value of the difference was used for analyzing data. The results showed that profitability and leverage do not have effect to sustainability report disclosure. Firm size has a negative significant effect on sustainability report disclosure. The board of commissioners moderates the relationship between profitability and leverage toward sustainability report disclosure, but cannot moderate the relationship between firm size toward sustainability report disclosure. This study concludes that the firm size influences sustainability report disclosure and the board of commissioner moderates the relationship between profitability and leverage toward sustainability report disclosure. It shows that corporate governance has an important role on sustainability report disclosure. The effectiveness of corporate governance indicates that company management can fulfill the firm’s goals and stakeholder needs. Keywords: Corporate Governance; Firm Size; Leverage; Profitability; Sustainability Report